The New Testament scholarship of Erasmus : an introduction with Erasmus' prefaces and ancillary writings - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974 ;, 2019)
CWE 41 is intended as an essential companion to the full range of Erasmus scholarship on the New Testament, as it is translated, annotated and presented in Volumes 42-60.